Performance of baited traps for integrated management of Hypothenemus hampei Ferrari (Coleoptera: Scolytinae) in a conilon coffee crop in Rondônia State, Brazil - De Souza, Moisés Santos; Costa, José Nilton Medeiros; Espindula, Marcelo Curitiba; Silva, Alexandre de Almeida e (EntomoBrasilis, 2020)
Hypothenemus hampei (Ferrari) is an important pest worldwide. Methods of monitoring and control using baited traps are not yet established in coffee plantations in the Brazilian Amazon. The objective of this work was to record, for the first time, results of the use of baited traps in coffee plantation located in Rondônia, in favor of the control and pest monitoring. Two areas were delineated: i) with use of the traps baited with ethanol/methanol (1:1), treatment; ii) without use of traps (control). For comparison of results, two factors were considered: damaged fruits (damage by H. hampei) and infested (H. hampei inside of fruits). It was observed higher levels of damaged fruits per plants in the control area compared to the area where traps were used. The density of the pest population per plants found on infested fruits was also higher in the control area compared to the trapping area. These results suggest that traps baited with ethanol/methanol (1:1) are an effective alternative for population control of pest also in the coffee plantations in Rondônia, where there is no such management with this tool. Use of the baited traps to monitor the insect accurately revealed that the flight stimulus of the colonizing females is influenced by values of the environmental variables. According to the results, colonizing females are more active in the afternoon. Therefore, in order to achieve more efficient control of H. hampei, the best time to apply control agents is between 2:00 pm and 6:00 pm.